2021
DOI: 10.1002/jmri.27475
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of MR Elastography in the Healthy Brain: Repeatability, Reliability, and Effect of Different Reconstruction Methods

Abstract: Background Changes in brain stiffness can be an important biomarker for neurological disease. Magnetic resonance elastography (MRE) quantifies tissue stiffness, but the results vary between acquisition and reconstruction methods. Purpose To measure MRE repeatability and estimate the effect of different reconstruction methods and varying data quality on estimated brain stiffness. Study Type Prospective. Subjects Fifteen healthy subjects. Field Strength/Sequence 3T MRI, gradient‐echo elastography sequence with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Brain MRE results are generally reproducible when the same method is applied, but caution is warranted when comparing results across studies. 35 Summarizing results across studies is difficult due to variations in acquisition parameters, post-processing, study design, cohorts, and units. For example, variations in driving frequencies display different regions of the non-linear stress/strain relationship in viscoelastic bodies.…”
Section: Discussion Technical Challenges and Comments On Translationmentioning
confidence: 99%
“…Brain MRE results are generally reproducible when the same method is applied, but caution is warranted when comparing results across studies. 35 Summarizing results across studies is difficult due to variations in acquisition parameters, post-processing, study design, cohorts, and units. For example, variations in driving frequencies display different regions of the non-linear stress/strain relationship in viscoelastic bodies.…”
Section: Discussion Technical Challenges and Comments On Translationmentioning
confidence: 99%
“…In an earlier study using this MRE method in healthy subjects, MRE data quality, measured as the curl-divergence ratio, was found to be lower in the deep gray matter regions than in regions closer to the skull. The study found no significant correlation between this data quality and stiffness measurements (15). The existing studies differ with respect to both MRE hardware and reconstruction methods.…”
Section: Discussionmentioning
confidence: 61%
“…The repeatability, assessed as the coefficient of variation, has been measured to be 4 % for the employed MRE technique (15). This should be taken into account if comparing small stiffness differences between subjects or longitudinal tracking over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the piston, Figure 3 shows that most of them are rigid despite the poor sample coupling that results from it. To our knowledge few groups have design rigid form fitting piston which makes sense to access soft tissue like breast [49], but which is more questionable for the head [40,109]. Having a flexible formfitting piston could ensure better sample coupling, in particular when the piston is in contact with a soft surface.…”
Section: Pros and Cons About Current Mechanical Actuators For Mrementioning
confidence: 99%